The development of a performance hand wear and tools product innovation framework - Susan L. Sokolowski (Fashion and Textiles, 2020)
Abstract Humans wear products and use tools that interface with their hands to provide abrasion resistance, impact protection, grip, thermal comfort, and detailed maneuvers. The skills needed to design new and innovative products for the hand are multi-faceted. Academic programs in the US typically focus on soft goods (textile and apparel) or hard goods (industrial and product design/engineering) based design. Therefore, students often do not learn all of the available skills and technologies needed to design hand wear performance products because of the pedagogical split between the different academic disciplines. This case study outlines a three-phase innovation framework, for use by designers throughout the product creation process, specifically for creating performance products and tools for the hand. The phases include strategies for: (1) understanding the hand wear and tool project background, (2) defining the user’s 3D and 2D hand and (3) hand wear and tool product innovation. The paper will also demonstrate how the framework was implemented by students in a graduate level design studio, to create new gloves for athletes. The framework could also be used by students and professionals to design innovative products for other users and to improve safety and overall performance.